The role of phosphodiesterase 4B in IL-8/LTB4-induced human neutrophil chemotaxis evaluated with a phosphodiesterase 4B inhibitor - Suzuki Osamu; Goto Taĳi; Yoshino Toshiharu; Nakamura Satoshi; Maeda Hiroaki (Acta Pharmaceutica)
PDE4B was previously shown to be a dominant PDE4 subtype of neutrophils. However, its physiological role in the neutrophil function has not been evaluated. In this study, the inhibitory effects of a phosphodiesterase 4B (PDE4B)- selective inhibitor (compound A) and subtype non-selective PDE4 inhibitors (roflumilast and cilomilast) were evaluated in human peripheral blood cells. Compound A, roflumilast and cilomilast in a similar manner inhibited TNF-α production by LPS-stimulated human mononuclear cells. However, the inhibitory effect of compound A on IL-8 or LTB4-induced chemotactic response of neutrophils was modest even at the highest concentration (10 μmol L-1), whereas roflumilast and cilomilast inhibited IL-8 or LTB4-induced neutrophil chemotaxis. Our results suggest that PDE4B does not play an important role during the chemotactic response of human neutrophils.